Metastatic melanoma presenting as undifferentiated tumour of unknown primary site: an immunohistochemical algorithm - Leila ALI; Valentin MOLDOVAN; Diana DEREWICZ; Octav GINGHINA; Maria SAJIN; Mariana COSTACHE (Archives of the Balkan Medical Union, 2019)
Introduction. The identification of the type and site of origin in undifferentiated tumours of unknown primary site using immunohistochemistry is a frequent requirement in pathology practice. There are many histologic lesions that display similar morphologic aspects, with misdiagnosis potentially resulting in over- or undertreatment. This makes the diagnostic accuracy extremely important in the era of targeted therapies.